Hyperconjugation in Carbocations, a BLW Study with DFT approximation - Humbel, Stephane; Alamiddine, Zakaria (Frontiers in Chemistry, 2014)
The geometry of ethyl cation is discussed with a high level optimization (CCSD/cc-pvQZ), and the hyperconjugation effect in carbocations is evaluated at the B3LYP/6-311G(d) level. The Block Localized Wavefunction (BLW) method is used for all evaluations of the hyperconjugation, considered as the energy gained by the delocalization onto the C+ atom. This energy is defined as the energy difference between the delocalized (standard) calculation, where the electrons are freely delocalized, and a localized form where the positive charge sits on the carbon center. It is evaluated for 18 carbocations, including conjugated systems. In these cases we were particularly interested in the additional stabilization brought by hyperconjugative effects. Among other effects, the β-silicon effect is computed. Hyperconjugation amounts in several cases to an energy similar to conjugation effects.